1987
DOI: 10.1149/1.2100515
|View full text |Cite
|
Sign up to set email alerts
|

The Photoelectrochemical Kinetics of n‐Type Cadmium Sulfide: I . The Hydroquinone System

Abstract: The photoelectrochemical kinetics of the oxidation of hydroquinone on n‐type cadmium sulfide have been studied using the ring‐disk electrode, photocurrent transients, and modulated light experiments. The balance between the faradaic reaction and the photocorrosion of the normalCdS has been investigated. The data are explained by a mechanism involving two surface intermediates. The potential dependence of the rate constants for surface recombination, for the oxidation of hydroquinone, and for the photocorrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Details of many photoelectrochemical reactions in general have been successfully investigated using dynamic photoelectrochemical methods. 8 Photocurrent transient methods [9][10][11][12][13][14][15] and intensity modulated photocurrent spectroscopy (IMPS), 8,10,[16][17][18][19][20][21][22] where the working electrode is illuminated with sinusoidally modulated light, have been used for this purpose in particular. These methods can be employed to measure the rate constants of charge transfer and recombination processes occurring at the semiconductor/electrolyte interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Details of many photoelectrochemical reactions in general have been successfully investigated using dynamic photoelectrochemical methods. 8 Photocurrent transient methods [9][10][11][12][13][14][15] and intensity modulated photocurrent spectroscopy (IMPS), 8,10,[16][17][18][19][20][21][22] where the working electrode is illuminated with sinusoidally modulated light, have been used for this purpose in particular. These methods can be employed to measure the rate constants of charge transfer and recombination processes occurring at the semiconductor/electrolyte interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that there is competition between the faradaic reaction and recombination as given in the model in the Theoretical section (3). We have shown that there is competition between the faradaic reaction and recombination as given in the model in the Theoretical section (3).…”
Section: Cmentioning
confidence: 71%
“…We (1) and others (2)(3)(4)(5) have also shown how redox kinetics at this overlayer plays a crucial role in the solar-conversion efficiency of devices based on this "heterojunction-photoelectrode" concept. We (1) and others (2)(3)(4)(5) have also shown how redox kinetics at this overlayer plays a crucial role in the solar-conversion efficiency of devices based on this "heterojunction-photoelectrode" concept.…”
Section: Cmentioning
confidence: 88%
See 2 more Smart Citations